Rheological Modeling and Characterization of Ficus platyphylla Gum Exudates - Nnabuk O. Eddy; Paul O. Ameh; Casimir E. Gimba; Eno E. Ebenso (Journal of Chemistry)
Ficus platyphylla gum exudates (FP gum) have been analyzed for their physicochemical parameters and found to be ionic, mildly acidic, odourless, and yellowish brown in colour. The gum is soluble in water, sparingly soluble in ethanol, and insoluble in acetone and chloroform. The nitrogen (0.39%) and protein (2.44%) contents of the gum are relatively low. The concentrations of the cations were found to increase according to the following trend, Mn>Fe>Zn>Pb>Cu>Mg>Cd>Ca. Analysis of the FTIR spectrum of the gum revealed vibrations similar to those found in polysaccharides while the scanning electron micrograph indicated that the gum has irregular molecular shapes, arranged randomly. The intrinsic viscosity of FP gum estimated by extrapolating to zero concentrations in Huggins, Kraemer, Schulz-Blaschke, and Martin plots has an average value of 7 dL/g. From the plots of viscosity versus shear rate/speed of rotation and also that of shear stress versus shear rate, FP gum can be classified as a non-Newtonian gum with characteristics-plastic properties. Development of the Master_s curve for FP gum also indicated that the gum prefers to remain in a dilute domain (C<C∗), such that 𝜂sp𝛼C1.2. The apparent activation energy of flow for FP gum (calculated from Arrhenius-Frenkel-Eyring plot) was relatively low and indicated the presence of fewer inter- and intramolecular interactions.